The Determinants of the Socioeconomic Inequality and the Trajectory of Child Stunting in the Philippines - Valerie Gilbert Ulep; Jhanna Uy; Lyle Casas; Mario V. Capanzana; Alice Nkoroi; Rene Gerard Galera; Maria Evelyn Carpio; Frederich Tan (Philippine Institute for Development Studies (PIDS), 2023)
About a third of Filipino children are stunted or chronically malnourished. However, there is a paucity of evidence on the socioeconomic inequalities of stunting in the Philippines. This study has two objectives. First, we discuss the wide range of determinants that explain the large socioeconomic disparity in stunting. Second, we model the trajectory of stunting until 2030 should the country expand the coverage of key nutrition and health interventions. Based on our previous decomposition analysis, maternal nutritional status and education factors, quality of prenatal care, and child diet are significant drivers of the disparity. Furthermore, using a compartment-based model, we expect a 10-percentage point reduction in the prevalence of stunting with expansive promotion of infant and young child feeding (IYCF) practices and complementary food interventions. Addressing the socioeconomic disparity in child stunting and universal provision of nutrition and health interventions puts the country on track of its 2030 Sustainable Development Goal (SDG) target.
Keywords: 330; undernutrition; child stunting; stunting projection; Philippines